Donald Trump isolationist doctrine “America first”: A case study of the US withdrawal from Afghanistan. - Mekkari Imene.Benziane Yasmine, FARRAH SABAH (UNIVERSITY OF MOHAMED BOUDIAF, 2022)
Abstract The US 2016 presidential elections brought Donald Trump as the 45th US President. Although the latter has been criticized of his personality and foreign intervention in manipulating the US elections, President Donald Trump has been identified of his doctrine; namely, „America first‟. As a matter of fact, Trump‟s Doctrine focused on amending and reconstructing the US domestic affairs, rather than focusing on foreign issues. The primary issue of in Trump‟s doctrine „America first‟ was resolving the issue of the US presence in Afghanistan. After fighting Al Qaeda and the Taliban there under the global War on Terror for twenty years, the US administration, under the direction of President Donald Trump, held peace talks and negotiations with the Taliban which resulted in the US withdrawal from Afghanistan in 2021.The present paper attempts to analyze Trump‟s isolationist Doctrine „America first‟ and how it affected the US decision of withdrawing from Afghanistan after twenty years of fighting terrorism there. In addition, the study highlights the implications of the US withdrawal from Afghanistan.
Keywords: Key words: Afghanistan, War on Terror, Donald Trump, America First, US withdrawal.